I'm not a mourning person : braving loss, grief, and the big messy emotions that happen when life falls apart - Carr, Kris (Hay House, Inc., 2023)
"A few years ago, Kris Carr's world was falling apart. Her father was dying, she had to pivot her business because of the pandemic, and she was on the verge of reaching her twenty-year milestone of living with an incurable Stage IV cancer diagnosis. While sitting in a CVS parking lot, she broke down, finally allowing herself to feel the massive stress and sadness she had been suppressing in order to seem strong for those around her, and for herself. And then she asked herself, "If embracing my intense emotions helped me feel even the slightest bit better, why was I so determined to avoid them? And given how all-encompassing this hint of catharsis felt, where else in my life have I been avoiding grief?" In this book, Kris shares her (embarrassing, painful, helpful, hilarious, and sometimes inappropriate) stories and observations about what to expect when you're not expecting your world to fall apart. If your life has been turned upside down-whether it be the dissolving of a relationship or marriage, the end of a job or career, any other number of significant unexpected transitions. . . or, like Kris, you are wrestling with the pain that comes from an illness or the death of a loved one, this book is filled with real-life experiences, practices, and insights that can help you feel better-not cured-but better. It will provide comfort and community as you learn that these big messy emotions can be a catalyst to take inventory of your life, figure out what matters most, and reset. . . because as Kris says, "when we're brave enough to tend to our hearts: Our messy emotions can teach us how to be free-not free from pain, but free from the fear of pain and the barrier it creates to fully living.""--